Molecular evidence of Rickettsia slovaca in spleen of wild boars in northeastern Algeria. (July 2018) - Zeroual, F.; Leulmi, H.; Bitam, I.; Benakhla, A.
Abstract: Using molecular assays, Rickettsia slovaca, the agent of a spotted fever group rickettsiosis resulting in scalp eschar and neck lymphadenopathy after tick bite, was assessed in 92 spleens recovered from 117 wild boars hunted in the far northeast of Algeria. Rickettsia slovaca was detected in 5.4% of tested wild boar spleens. The presence of R. slovaca DNA in boar spleens questions the relationship that may exist between this bacterium and Sus scrofa algira, and its role in human infections.